2021
DOI: 10.17762/turcomat.v12i5.1800
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Statistical Literacy Level of Postgraduate Education Research Students in Malaysian Research Universities

Abstract: Statistical literacy is an essential component of research literacy demanded for the research students to master as they are required to read, comprehend, and evaluate research articles. Misinterpretations of data and research findings are among the unfavorable results in the lack of research literacy. Consequently, it will affect the quality of their research and eventually leads to ripple impact on other researchers. However, this study is still under researched especially among postgraduate research student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, past research has shown that the majority of students from primary school to tertiary level have misunderstandings and difficulties to acquire numerous statistical concepts and skills. These include statistical graph complexity and reading (Arteage et al, 2015), interpretation of box plots (Pierce & Chick, 2013), data representation (Chick & Pierce, 2012;Saidi & Siew, 2019;Ibnatul et al, 2021;Subanji et al, 2021), and descriptive statistics (Chan, et al, 2013), variability (delMas & Liu, 2005Matthew & Clark, 2007), distribution (Lee & Meletiou-Mavrothesis, 2003), measures of central tendency (Cooper & Shore, 2008;Olani et al, 2011). Malaysian form four students tend to have inferior statistical reasoning abilities, claimed Chan and Zaleha (2014), Krishnan and Noraini (2014).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…However, past research has shown that the majority of students from primary school to tertiary level have misunderstandings and difficulties to acquire numerous statistical concepts and skills. These include statistical graph complexity and reading (Arteage et al, 2015), interpretation of box plots (Pierce & Chick, 2013), data representation (Chick & Pierce, 2012;Saidi & Siew, 2019;Ibnatul et al, 2021;Subanji et al, 2021), and descriptive statistics (Chan, et al, 2013), variability (delMas & Liu, 2005Matthew & Clark, 2007), distribution (Lee & Meletiou-Mavrothesis, 2003), measures of central tendency (Cooper & Shore, 2008;Olani et al, 2011). Malaysian form four students tend to have inferior statistical reasoning abilities, claimed Chan and Zaleha (2014), Krishnan and Noraini (2014).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Studies examining the effect of gender on statistical literacy are relatively rare [14]. Previous study [15] found that both male and female participants' statistical literacy levels were still low even though they were postgraduate students. In addition, there was no statistically significant difference in literacy skills by gender [16].…”
Section: Introductionmentioning
confidence: 99%